2021
DOI: 10.3389/fpubh.2021.745630
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Confidence and Hesitancy at the Start of COVID-19 Vaccine Deployment in the UK: An Embedded Mixed-Methods Study

Abstract: Background: Approval for the use of COVID-19 vaccines has been granted in a number of countries but there are concerns that vaccine uptake may be low amongst certain groups.Methods: This study used a mixed methods approach based on online survey and an embedded quantitative/qualitative design to explore perceptions and attitudes that were associated with intention to either accept or refuse offers of vaccination in different demographic groups during the early stages of the UK's mass COVID-19 vaccination progr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
1
29
0
6
Order By: Relevance
“…These perceptions are at odds with the official government communication that recommends vaccines. Low trust in government has been reported to be associated with COVID-19 vaccine rejection [ 31 ]. Public health risk communication messages must convey accurate and objective knowledge and understanding of risks and hazards that affect health to diverse audiences [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions are at odds with the official government communication that recommends vaccines. Low trust in government has been reported to be associated with COVID-19 vaccine rejection [ 31 ]. Public health risk communication messages must convey accurate and objective knowledge and understanding of risks and hazards that affect health to diverse audiences [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic caused a major global health, social, and economic crisis. At the end of December 2020, the approval of the first vaccine started the global vaccination program, which restored minimal confidence in the population [ 97 ]. The scientific community is convinced that, without a broad and comprehensive vaccination program, it will be impossible to overcome COVID-19.…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%
“…In their study of psychological factors associated with COVID-19 vaccine hesitancy and resistance in Ireland and the United Kingdom, Murphy et al (2021) found that those who were vaccine hesitant, as well as those who were resistant, were more self-serving, held strong religious viewpoints, and held an internal locus of control. Another study from the U.K. that provided examples of other contributors, cited mistrust in politicians and science ( Roberts et al, 2021 ). Additional factors to vaccine hesitancy, particularly in the U.S., included vaccine safety, vaccine effectiveness, anxiety over potential side effects, and mistrust of the healthcare system and government ( Khubchandani et al, 2021 ; Pogue et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%